Impact of ciprofloxacin and coenzyme Q10 on spermatogenesis in mice - Reshna Kamal Albarzanji; Shatha Saeed Zakar; Nidhal Abdulkader Mohammed Ali (Medical Journal of Babylon, 2022)
Background: Ciprofloxacin is commonly used to treat many bacterial infections. There are controversial reports regarding abnormalities in sperm parameters in laboratory animal and human studies after ciprofloxacin administration. Coenzyme Q10 is a fat-soluble vitamin-like substance that is concentrated in sperm mitochondria, where it acts as an antioxidant and an energy promoter. Various studies found that coenzyme Q10 can improve sperm parameters, whereas other studies showed no significant improvement in sperm parameters. This study aimed at investigating the effect of ciprofloxacin and coenzyme Q10 on spermatogenesis and sperm morphology in male mice. Materials and Methods: Twenty eight-week-old male albino mice were randomly divided into four equal groups: control group, group 1 that received ciprofloxacin (102.78 mg/kg), group 2 that was given coenzyme Q10 (20.56 mg/kg), and group 3 that was given both ciprofloxacin and coenzyme Q10. The drugs were given twice daily for 35 days. On day 36, the mice were sacrificed; sperm were harvested, analyzed for sperm morphology, and stained for detection of sperm abnormalities. Testes were taken to evaluate spermatogenesis histopathologically. Data were statistically analyzed, and a P value of ≤ 0.05 was considered significant. Results: Sperm morphology showed no significant alteration in the groups treated with ciprofloxacin, coenzyme Q10, and a combination of ciprofloxacin and coenzyme Q10 compared with the control. However, histopathological lesions showed a mild decrease in spermatogenesis that was accompanied by mild vein congestion in the testicular tissue sections of mice treated with ciprofloxacin only. Conclusion: Ciprofloxacin had no significant negative impact on sperm morphology; however, it induced mild histopathological alterations in testicular tissue that was ameliorated by the coadministration of coenzyme Q10. This effect should be taken into consideration during ciprofloxacin therapy in males.